2006
DOI: 10.1111/j.1551-2916.2006.01241.x
|View full text |Cite
|
Sign up to set email alerts
|

Monazite Coatings on SiC Fibers II: Oxidation Protection

Abstract: The effect of monazite on the oxidation of SiC was studied in laboratory and dry air. Monazite inhibited the oxidation of Tyranno‐SA™, Tyranno‐ZX™, Sylramic, and Hi‐Nicalon SiC fibers. Oxidation of pure chemical vapor deposition SiC and undoped SiC single crystals was not inhibited by monazite. Dry oxidation of both uncoated and monazite‐coated Tyranno‐SA™ fibers initially displayed parabolic kinetics with an activation energy of 180–190 kJ/mol. Subsequently, the oxidation rate of monazite‐coated fibers increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 87 publications
3
30
0
Order By: Relevance
“…Mogilevski et al reported parabolic rate constants (K p ) of 30 nm 2 /min for oxidation of Tyranno SA3 TM fibres at a temperature of 1100 • C (exposure time: ≤ 20 h, dry air: ≤5 ppm H 2 O). 49 Taken this into account, silica with a thickness of ∼190 nm formed after 20 h at 1100 • C in dry air which is slightly lower than silica thickness measured in this study for an atmosphere with ∼2.7% water vapour content. Hence, in spite of full active oxidation of pyc-fibre coating, SiC-fibres being embedded in a relatively dense SiCN-matrix exhibit a significantly lower silica formation (at least 1/3) compared to single fibres without matrix.…”
Section: Microstructure Of Cmc Materialsmentioning
confidence: 70%
See 2 more Smart Citations
“…Mogilevski et al reported parabolic rate constants (K p ) of 30 nm 2 /min for oxidation of Tyranno SA3 TM fibres at a temperature of 1100 • C (exposure time: ≤ 20 h, dry air: ≤5 ppm H 2 O). 49 Taken this into account, silica with a thickness of ∼190 nm formed after 20 h at 1100 • C in dry air which is slightly lower than silica thickness measured in this study for an atmosphere with ∼2.7% water vapour content. Hence, in spite of full active oxidation of pyc-fibre coating, SiC-fibres being embedded in a relatively dense SiCN-matrix exhibit a significantly lower silica formation (at least 1/3) compared to single fibres without matrix.…”
Section: Microstructure Of Cmc Materialsmentioning
confidence: 70%
“…silica formation on Tyranno SA3 TM fibres after exposure (T = 1200 • C, t = 10 h) to laboratory air with a water vapour content of ∼1-1.6% (silica thickness ∼700 nm) is approximately 2.75 times higher compared to that in dry air (silica thickness ∼250 nm). 49 Considering water vapour content in the laboratory air of ∼2.7% in this study, a measured silica thickness of ∼215 nm on Tyranno SA3 TM fibres in SiC pyc /SiCN after exposure to air (T = 1100 • C, t = 20 h) is in the same range as silica thicknesses reported for single fibres in dry air. Mogilevski et al reported parabolic rate constants (K p ) of 30 nm 2 /min for oxidation of Tyranno SA3 TM fibres at a temperature of 1100 • C (exposure time: ≤ 20 h, dry air: ≤5 ppm H 2 O).…”
Section: Microstructure Of Cmc Materialsmentioning
confidence: 72%
See 1 more Smart Citation
“…Several oxidation resistant and crack-deflecting materials including monazite, alumina/silica, stabilized zirconia, and others were proposed as appropriate candidates for interphase zone in CMC's. [2][3][4][5][6][7][8] Some information is available in publications, describing the behavior of the stabilized ZrO 2 -coated SiC fibers exposed to air at high temperatures. 9,10 Preliminary studying of the peculiarities of morphology and nanorelief of two zirconia-coated fibers, namely, Hi-Nicalon TM and Tyranno-SA TM before and after exposition to air at 1000 • C using atomic force microscopy (AFM) and scanning electron microscopy (SEM) showed that these features are greatly dependent on the type of SiC fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the oxidation of these secondary species has to be considered as well. The oxidation of sintered SiC fibers belonging to the 3rd generation, like Hi-Nicalon S and Tyranno SA3 [22,23], has been extensively studied in Wright Patterson labs in dry and wet air [24][25][26][27]. They reported parabolic kinetics in both dry air and laboratory air during the initial oxidation stage at 1000-1200 • C, with an activation energy on the order of 180-190 kJ/mol, which is close to the value reported for the oxidation of single crystal 6H-SiC [25].…”
Section: Introductionmentioning
confidence: 99%